Residual stresses in MoN and Mo2N coatings deposited by arc PVD on high speed steel substrate - (:unkn) unknown (ASM INTERNATIONAL, 2002)
Polycrystalline MoN and MoN films have been deposited by chemical vapor deposition (CVD), magnetron sputtering and arc PVD techniques. They have interesting physical and mechanical properties, which made them candidates for wear and corrosion resistant coatings and diffusion barriers in microelectronics. The residual stresses in MoN and Mo2N films consist of thermal stress and growth stress or intrinsic stress generated during deposition. The magnitude of measured residual stress in the film depends on process parameters such as temperature, bias voltage, gas pressure, substrate, deposition time, and film thickness. It is important to measure residual stresses in the MoN and MoN coating to estimate and interpret the adhesion, wear and hardness correctly. Residual stresses in these coatings were measured by XRD using the Rocking and the Fixed Incident Multiplane techniques. Residual stresses in Mo2N (f.c.c) and in MoN (hexagonal) films were about 5 and 10 GPa (compressive) respectively. These results were discussed with respect to the elastic constant, crystal structure and deposition condition of MoN and Mo2N films.
Keywords: MECHANICAL-PROPERTIES; HARD COATINGS; THIN-FILMS; EVAPORATION; TIN